2021
DOI: 10.1002/bit.27757
|View full text |Cite
|
Sign up to set email alerts
|

White paper on high‐throughput process development for integrated continuous biomanufacturing

Abstract: Continuous manufacturing is an indicator of a maturing industry, as can be seen by the example of the petrochemical industry. Patent expiry promotes a price competition between manufacturing companies, and more efficient and cheaper processes are needed to achieve lower production costs. Over the last decade, continuous biomanufacturing has had significant breakthroughs, with regulatory agencies encouraging the industry to implement this processing mode. Process development is resource and time consuming and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 98 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…33 The crucial element for PAT application in a continuous downstream process is to gather real-time information for process control. 75,82 However, especially for the chromatography steps, implementing PAT can be challenging because of the typical short process times (in the time frame of minutes). 62 Rathore et al demonstrated that, with on-line analytical liquid chromatography (with the measurement performed in 30 min), continuous monitoring of the chromatography step for aggregate peaks can be achieved.…”
Section: Design Constraints For the Miniaturization Of A Pat Tool For Continuous Biomanufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The crucial element for PAT application in a continuous downstream process is to gather real-time information for process control. 75,82 However, especially for the chromatography steps, implementing PAT can be challenging because of the typical short process times (in the time frame of minutes). 62 Rathore et al demonstrated that, with on-line analytical liquid chromatography (with the measurement performed in 30 min), continuous monitoring of the chromatography step for aggregate peaks can be achieved.…”
Section: Design Constraints For the Miniaturization Of A Pat Tool For Continuous Biomanufacturingmentioning
confidence: 99%
“…The crucial element for PAT application in a continuous downstream process is to gather real‐time information for process control 75,82 . However, especially for the chromatography steps, implementing PAT can be challenging because of the typical short process times (in the time frame of minutes) 62 .…”
Section: Design Constraints For the Miniaturization Of A Pat Tool For...mentioning
confidence: 99%
“…40 Unfortunately, these devices are not widely used in laboratories. 36 Most of these microdevices require a clean-room environment for their fabrication, 41 which is not available in most laboratories. Besides the lack of appropriate facilities, the cost and expertise to develop and fabricate such microdevices are another drawback.…”
Section: Introductionmentioning
confidence: 99%
“…35 Furthermore, it is important to highlight that microdevices can lead to more automated labs and miniaturized analyses. 36 Characterization of protein solutions using microdevices has been already described, 37,38 to select flocculating agents 39 or investigate protein phase behavior. 40 Unfortunately, these devices are not widely used in laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[6] However, these techniques are characterized by lengthy analysis times. [1,7] Fluorescent dyes, such as SYPRO Orange and 4-4-bis-1-phenylamino-8-naphthalene sulfonate (Bis-ANS), are sensitive to the hydrophobicity of the surrounding environment. Since aggregate formation generates hydrophobic unfolded protein structures, these fluorescent tags can be used to rapidly detect this phenomenon.…”
mentioning
confidence: 99%